Pengaruh Pemberian Mulsa Organik Terhadap Sifat Fisik dan Kimia Tanah serta Pertumbuhan Akar Kelapa Sawit - Antari, Rabisa; Manurung, Gulat ME; ', Wawan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Oil palm (Elaeis guineensis Jacq) is a multipurpose plant which occupies an important position generaly in agricultural sector and particularly in plantation sector. Bright prospects for palm oil commodity in the world encourage people to plant oil palm in acidic mineral soil, which could face some obstacles, on physical, chemical and biological soil properties. In the dry season, oil palm has the type of oil palm roots are shallow making it relatively less tolerant to drought. Because of these problems is an attempt to solve the problem in oil palm land by using organic mulch (oil palm empty fruit bunches, Calopogonium, palm midrib and ferns). This research has been carried out in the experimental farm of the Agriculture Faculty Riau University, from June to September 2012. The purpose of this study was to determine the effect of organic mulch on soil physical and chemical properties, as well as the root growth of palm oil using a randomized block design (RBD), that consists of 5 treatments and 3 replications. The results of this study shown that treated soil using organic mulch had the significant difference compare to soil without mulch in the whole observation parameters. Organic mulches can improve total pore space, C-organic, N-total, soil water content and soil temperature and decrease soil bulk density. It also, can increase the weight of the roots, root dry weight, root occupy and the plant root volume.  Keywords: Organic Mulch, Soil Physical and Chemical Properties, Palm Oil